2022
DOI: 10.1051/0004-6361/202243411
|View full text |Cite
|
Sign up to set email alerts
|

Quasars as high-redshift standard candles

Abstract: The non-linear relation between the X-ray and ultraviolet (UV) luminosity in quasars has been used to derive quasar distances and to build a Hubble diagram at redshifts up to z ∼ 7. This cosmological application is based on the assumption of independence of the relation on redshift and luminosity. We want to test the reliability of this hypothesis by studying the spectroscopic properties of high-redshift quasars in the X-ray and UV bands. We performed a one-by-one analysis of a sample of 130 quasars at z > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…This deviation favored a larger overall matter density fraction Ω m and an evolving dark energy equation of state. Similar results were obtained by the same method in subsequent works using quasar samples at higher redshifts (Salvestrini et al 2020), incorporating additional X-ray quasar catalogs (Sacchi et al 2022;Lusso et al 2020;Bisgoni et al 2021) and joint analyses of quasars along with other cosmological probes (Bargiacchi et al 2022). These findings, if true, would be an important new procedure for using extragalactic sources with wide dispersion in their luminosity (i.e., sources far from being a "standard candle") for precision cosmological studies on par with near-standard candles like Cepheid variables and Type Ia supernovae, but extending to higher redshifts.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This deviation favored a larger overall matter density fraction Ω m and an evolving dark energy equation of state. Similar results were obtained by the same method in subsequent works using quasar samples at higher redshifts (Salvestrini et al 2020), incorporating additional X-ray quasar catalogs (Sacchi et al 2022;Lusso et al 2020;Bisgoni et al 2021) and joint analyses of quasars along with other cosmological probes (Bargiacchi et al 2022). These findings, if true, would be an important new procedure for using extragalactic sources with wide dispersion in their luminosity (i.e., sources far from being a "standard candle") for precision cosmological studies on par with near-standard candles like Cepheid variables and Type Ia supernovae, but extending to higher redshifts.…”
Section: Introductionsupporting
confidence: 80%
“…We find in Section 2 that the method of determining the luminosity distance as a function of redshift (and hence cosmological parameters) from the observed (nonlinear) correlation between two luminosities or fluxes in a population quasars, proposed by RL and utilized in the subsequent works, Salvestrini et al (2020), Sacchi et al (2022), andBisgoni et al (2021), suffers from a fatal logical inconsistency inherent in the method. It is either circular or tautological.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Image reproduced with permission from Lusso et al (2020), copyright by ESO Table 3 Summary of the cosmological constraints for the combined quasars (Lusso et al 2020) and supernovae Ia (Scolnic et al 2018) sample for three different cosmological models: flat KCDM, open KCDM (oKCDM) and flat w 0 À w a CDM (see Bargiacchi et al 2021a slope with distance). This point has been recently discussed also by Sacchi et al (2022), who demonstrated that a one-by-one spectral analysis of a sample of quasar at redshift higher than 2.5, with high-quality X-ray and UV observations, further reduces the dispersion from 0.2 dex (by employing photometric data only) to 0.12 dex, whilst the observed slope of the relation is still around 0.6. Sacchi et al (2022) also showed that the composite X-ray and UV spectra of these high-redshift quasars do not show any peculiar spectral feature or systematic difference with respect to the average spectra of quasars at lower redshifts.…”
Section: Basic Idea and Equationsmentioning
confidence: 58%
“…This point has been recently discussed also by Sacchi et al (2022), who demonstrated that a one-by-one spectral analysis of a sample of quasar at redshift higher than 2.5, with high-quality X-ray and UV observations, further reduces the dispersion from 0.2 dex (by employing photometric data only) to 0.12 dex, whilst the observed slope of the relation is still around 0.6. Sacchi et al (2022) also showed that the composite X-ray and UV spectra of these high-redshift quasars do not show any peculiar spectral feature or systematic difference with respect to the average spectra of quasars at lower redshifts. The absence of any spectral variance between high-and low-redshift quasars, combined with the tightness of the X-ray to UV relation, suggests that no evolutionary effects are present in the relation itself.…”
Section: Basic Idea and Equationsmentioning
confidence: 58%
“…This may be a sign that quasars cannot be treated as the standard candle if the L X -L UV relation is used (Khadka & Ratra 2020b) and there have already been some discussions and controversies about this (Yang et al 2020;Banerjee et al 2021;Dainotti et al 2022;Li et al 2022;Petrosian et al 2022;Singal et al 2022). Furthermore, some data show evidence of redshift evolution of the X-ray and UV correlation (Khadka & Ratra 2022), although recently Sacchi et al (2022) found that this correlation still holds at z > 2.5 by performing a one-by-one analysis of a sample of 130 quasars with high-quality X-ray and UV spectroscopic observations. Therefore, it remains interesting to research the possible redshift evolution of the L X -L UV relation.…”
Section: Introductionmentioning
confidence: 99%